The relationship between eye-hand coordination and flexibility of the arm muscles with the accuracy of the table tennis forehand smash - Muhammad Fiqi Firmanda; Sugiarto Sugiarto (Sriwijaya Journal of Sport, 2023)
The research problem is that many athletes make mistakes such as the ball getting caught in the net and when the ball crosses the net, but the ball comes out of the table. This study aims to determine 1) the relationship between eye-hand coordination (X1) and the accuracy of the forehand smash (Y), 2) the relationship between arm muscle strength (X2) and the accuracy of the forehand smash (Y). 3) the relationship between hand-eye coordination (X1) and arm muscle strength (X2) with the accuracy of the forehand smash (Y). The method used in this research is correlational. The sample consisted of athletes from the PTM Dwi Bengawan table tennis club, which consisted of 17 male athletes. The research instruments were throwing and catching a tennis ball test, measuring the strength of the arm muscles using an expanding dynamometer, and testing the accuracy of the forehand smash. Data analysis used prerequisite tests for normality and linearity. Test the hypothesis using SPSS. The results show that there is a relationship between hand-eye coordination (X1) and the accuracy of the forehand smash (Y) with a value of r count = 0.674 > r table = 0.482. In addition, there is also a relationship between arm muscle strength (X2) and the accuracy of the forehand smash (Y), with a value of r count = 0.781 > r table = 0.482. There is a relationship between eye-hand coordination and arm muscle strength on the accuracy of the forehand smash with an F count = 12.197 > F table = 3.74. It is hoped that further research can discuss matters that affect the accuracy of the forehand smash in table tennis in terms of biomechanics.